Influenza and respiratory care - Pokorski, Mieczyslaw (Advances in experimental medicine and biology ;, 2017)
Respiratory infections constitute a major public health concern. The goal of this book is to share knowledge on the best advances in influenza and influenza-like viral infections, and new molecular-based diagnostic methods that discern the antigenic shift enabling viruses to constantly evolve and elude the host immune response. Co-infections, co-morbidities, persistently meager anti-flu vaccination coverage, and infection complications are dealt with. The chapters also further insight into such topics as the effects of sex hormones, and socioeconomic and anthropometric measures on respiratory and immune functions underlying the severity of asthma and respiratory allergy. Psychological functioning in respiratory disorders, taking into account quality of life, illness acceptance, and depressive symptoms is also reviewed as it is all too often underestimated by healthcare providers. The book is intended for clinicians, researchers, students, and all other actors in health-related issues.